Qualidade da evidenciação contábil de informações ambientais decorrentes dos serviços de gestão dos resíduos sólidos urbanos prestados pelas capitais brasileiras - Renata Luciana dos Reis Magalhaes (2013)
Environmental issues are a high challenge in terms of social responsibility, including its impact on the accounting disclosure. Such matters involve judgment and specific expertise from different areas of knowledge and therefore should receive the contribution of each area,especially the Accounting that aims to provide useful information including on the environmental impacts that result from economic activity of public entities. The information quality was considered and treated here as information result containing qualitative characteristics exposed by the Conceptual Structure of Accounting (CPC-Comitê de Pronunciamentos Contábeis (Accounting Pronouncements Committee), 2011). In the background, this research aims to check the literature concerning the way this environmental disclosure can happen on public entities and to seek which environmental information arising from management services has been evidenced by the accountability of the Brazilian State capitals regarding the urban solid waste produced in their jurisdiction. Furthermore, the primary objective of this study was to subject the available information to be examined by the stakeholders of the Municipality of Belo Horizonte, Minas Gerais State, Brazil, and, so, assess its quality. This research is characterized as explanatory regarding the objectives, and bibliographic, documentary, and of survey regarding the procedures with qualitative and quantitative approach to the problem. The proposed methodological proceeding was divided into two stages. Information disclosed by all 27 Brazilian State capitals were analyzed and pilot interview was performed in certain municipality of Minas Gerais State for the knowledge and understanding the theme. The methodology construction for analyzing the information quality was based on judgments made by selected stakeholders who responded an evaluation form in order to judge the quality of the environmental accounting report of Belo Horizonte. This city was chosen to favor the best selection of evaluators and have better access to them. Many users were invited to attend who have expressed interest in environmental accounting information from Belo Horizonte Municipality; volunteers wereselected among members of the Court, Committee of the Environment and Urban Policy of Legislature Power, Environmental Councils, researchers of Accounting and environment, public employees from Accounting and environment sector, and accountants and/or personsconnected to the environment. Through descriptive analysis of the collected data, it was possible to create a methodology for classification of environmental accounting information in quality levels, divided into One, Three or Five Stars. The findings show that among the 27 analyzed portals, the municipality of Federal District advanced in its path and themunicipalities of Belo Horizonte, Campo Grande, Curitiba, and Florianópolis started their trajectories, but far short of what might be called an ideal disclosure. Based on the quality assessment step of environmental accounting information provided by the Municipality ofBelo Horizonte in 2011, it was concluded that such information has been mostly classified A Star, i.e., it did not meet users' needs, keeping them dissatisfied. Information that met the users' needs, classified Three Stars, reported up basically the only financial information. The information that met the users' needs and exceeded their expectations and, therefore, classified as Five Stars, was only the identification of the counter in charge. Conclusions about what information kind could satisfy user's needs and which information does not show any usefulness to users were measured under the aspects of relevance, reliability, comparability,verifiability, timeliness, and understandability (CPC, 2011).